Financial development and the end-use of migrants' remittances - Michael Coon (IZA Journal of Labor & Development, 2014)
This study examines how the level of financial development in a community affects households' decisions over how remittance income is spent. My findings suggest that in communities without banks remittances are more likely to be used for productive investments or to purchase assets. Increasing the size of the financial sector in communities with banks present increases the likelihood that remittances are used for productive investment and decreases the likelihood that remittances are used for general consumption. Finally, I find that the services offered by banks also affect the likelihood of using remittances for productive investment, purchasing assets, and general consumption.
Keywords: F24; G21; D19; 330; Remittances; Financial development; Mexico